Trade, poverty, and social protection in developing countries - Raj M. Desai; Nita Rudra (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
How do shifts in trade affect social protections for the poor? Although the fraction of the world's population considered the 'extreme' poor has fallen by over one-half over the past quarter century, many of those lifted above the global poverty line remain vulnerable to shocks that could place them back into poverty. These are the groups that require social protection to stabilize their incomes. Among the shocks to which the absolute poor have been exposed are those created by trade liberalization, particularly in the agricultural sector. The resulting risks, uncertainties, and significant threats to social stability from this type of trade require that the poor are provided with some forms of adjustment assistance. We examine the effects of trade movements on several dimensions of social protection, including spending, coverage, and adequacy over the past two decades. We find that, contrary to previous studies, disaggregating trade may be key to determining which international market variables drive expansion of social protections for the poor. Examining trade in agricultural goods reveals that net food and agricultural exporters provide better social protection than countries that report food deficits. We reason that although both food importers and exporters are vulnerable to shocks, net food exporters generate relatively more revenues to invest in social programs.
Keywords: F60; I38; Q17; 330; globalization; social protection; trade